Frequency of Hearing Impairment in Siblings of Hearing Impaired Children - Umair Nasir, Muhammad Ahmed, Azam Khan, Saira Zaman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: It has been reported that hearing impairment is significantly associated with multiple negative outcomes including depression, loneliness, altered self-esteem, and diminished functional status. The deaf and hard of hearing community is very diverse as for as cause, age of onset and degree of hearing loss. Aim: To determine the frequency of hearing impairment in siblings of hearing impaired children. Methods: This is descriptive observational study was conducted between September 2015 to February 201 at FMH College of Medicine and Dentistry. A total of 100 hearing impaired children aged between 4 to 20 years were included in this study. A self-designed questionnaire was used to assess the parental point of views. The questionnaire was designed as a data collection tool in order to collect the frequency from the HIC regarding their siblings hearing impairment. Results: Results indicated that out of 100 subject 63(63%) were male and 37(37%) were female and the mean age of patients was 12.28±4.13 years. On asking the HIC about total number of siblings 15(15%) responded that they had only 1 sibling, 28(28 %) responded that they had only 2 siblings, 17(17%) responded that they had only 3 siblings, 17(17%) responded that they had only 4 siblings, 14(14%) responded that they had only 5 siblings, 1(1%) responded that they had only 6 siblings and 8(8%) responded that they had only 7 siblings. Conclusion: It was concluded from the above study that frequency of hearing impairment in siblings of hearing impaired children is in high proportion and this high proportion of hearing impairment is because of cousin marriages, pressure due to family structure, genetic change.